The effect of proprioceptive exercises on balance sedentary students - P. Reddy; R.R>J. Van Bever Donker; J. Wakelin; S. Sigamoney; T. Mkhize; S. Moodley; N. Mthuli (AOSIS, 2014)
The increasin prevalence of sedentism in South Africa is a cause for concern, as it has been linked to the development of many health conditions and balance disturbances.